2019
DOI: 10.3389/fonc.2019.01253
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Bioactive Chemerin by Keratinocytes Inhibits Late Stages of Tumor Development in a Chemical Model of Skin Carcinogenesis

Abstract: Chemerin is a multifunctional protein acting mainly through the G protein-coupled receptor ChemR23/CMKLR1/Chemerin1. Its expression is frequently downregulated in human tumors, including in melanoma and squamous cell carcinoma of the skin and anti-tumoral properties of chemerin were reported in mouse tumor graft models. In the present study, we report the development of spontaneous skin tumors in aged ChemR23-deficient mice. In order to test the potential therapeutic benefit of chemerin analogs, a transgenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…To evaluate whether the site of expression of chemerin is of relevance for its anti-tumoral effects, we used a mouse model in which a bioactive form of chemerin is expressed under control of the keratin 5 promoter (K5-chemerin model). These mice were previously shown to express chemerin in basal keratinocytes of the skin, resulting in a significant increase of chemerin activity in the blood [ 40 ]. Following injection of B16 ( Figure 1C ) or LLC ( Figure 1D ) cells, K5-chemerin mice developed tumors significantly smaller than control mice in both tumor graft models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To evaluate whether the site of expression of chemerin is of relevance for its anti-tumoral effects, we used a mouse model in which a bioactive form of chemerin is expressed under control of the keratin 5 promoter (K5-chemerin model). These mice were previously shown to express chemerin in basal keratinocytes of the skin, resulting in a significant increase of chemerin activity in the blood [ 40 ]. Following injection of B16 ( Figure 1C ) or LLC ( Figure 1D ) cells, K5-chemerin mice developed tumors significantly smaller than control mice in both tumor graft models.…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenesis also plays a major role in tumor development, particularly in the late stages of progression in which chemerin was shown to act [ 40 ]. Histological analysis of the LLC and B16 tumors at different stages of growth uncovered the presence of necrotic areas predominating in the central parts of the tumors and increasing in size with time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein array analysis for cytokines and chemokines revealed that the levels of chemerin and nexin were mainly altered by knee loading in the serum of wild-type and knockout mice, as well as the responses to dopamine and cholesterol in tumor cells. It is reported that chemerin suppresses hepatocellular carcinoma metastasis, breast cancer growth, prostate cancer progression, skin carcinogenesis, and melanoma [ 36 , 37 , 38 , 39 , 40 ], while nexin is a stimulator of peritoneal metastasis in ovarian cancer [ 41 ], as well as the growth, migration, and invasion of breast cancer cells [ 42 ]. It is also reported that Wnt signaling in tumor cells is inhibited by chemerin while nexin is a downstream target of Wnt signaling [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%